An Eco-biometrical Study on Tiger in the Estuarine Eco-system of Sundarbans - Chakrabarti, Kalyan (Indian Forester, 1984)
This eco-biometrical study on tigers in the unique estuarine eco-system of Sundarbans has enabled to throw light into the unknown biological properties of the marshy terrain of Sundarhans and established some unique ecological relationship. between the man and the man-eater A bio-metrical prediction formula derived from the study also brought out relationships between the length and pugmark of tiger which wonld be of immense value in wild life management and research. The revealing facts of ecology perceptible from this study has surely opened up new vistas of thought and research into the wild life ecology of tiger and of the unique habitat of Sundarbans which is a proverbial name in the world with tigers on land and crocodiles on water. Estuarine tigers of Sundarbans are popularly called inherent man-eaters having high degree of cunningness. They took heavy toll of precious hnman lives (over ahout 300 in undivided Sundarbans a year). A Study ranging over a period of about fifteen yeas by the author since 1968 covering salinlty of soil, water, flora, fauna, predator-prey relationship enabled him to classify tigers according to their behaviours pattern (aggressive, circumstancial, etc.) and other biological aspects of the animal. Cuualty pattern among various professional forest workers were determined along with pattern in the method of kill, exact time of kill, choice of victim, their age etc. The pattern of activities of the animal was found to be somewhat 'rhythmic', remiiniscent of "endogenous self sustaining oscillation" that some estuarine organisms have. It was found that closure of the 'Core area' of project tiger to the permit holders provoked the animal to migrate to adjacent blocks in search of human food. Pugmarks were classified into five classes and a regression equation correlating the size of pugmarks with length of tiger was established. Salinity determination of water and soil by use of Spearman's rank correlation coefficient formula revealed remarkable closeness between human casualty and high degree of salinity. It was felt that the present study was extremely complicated in the diverse habitat and called for concerted research of scientists from various sphere of forestry and biology.